Pengaruh Photovoice Interactive terhadap Peningkatan Pengetahuan Penanganan Bencana Longsor pada Remaja - Evi Supriatun; Uswatun Insani; Ariani Indrastuti (Journal of Telenursing (JOTING), 2019)
The purpose of this study is to determine the effect of interactive photovoice on landslide disaster management knowledge in adolescents. This study uses a quasi experimental pre test and post test. T test results showed an increase in knowledge of landslide disaster management in adolescents compared with the control group (p value = 0,000). In conclusion, Photovoice interactive influences the knowledge of landslide disaster management in adolescent age groups in Salem District, Brebes Regency. Keywords: Landslide Disaster, Photovoice Interactive, Youth